The Group Cohesiveness Scale (GCS) for Psychiatric Inpatients - Tinakon Wongpakaran (2018)
Purpose: This study aimed to examine the psychometric properties of the seven-item Group Cohesiveness Scale (GCS). Design and Methods: In total, 96 inpatients completed the GCS along with the Cohesion to Therapist Scale Questionnaire and the Group Benefit Questionnaire after participating in group therapy sessions. Construct and concurrent validities and internal consistency were analyzed. Findings: It yielded a Cronbach's alpha of .87, with a one-factor solution with excellent fit indices. A significant correlation was found between the GCSc, the Cohesion to Therapist Scale, and the Group Benefit Questionnaire. Practice Implications: The scale shows good internal consistency, and its brevity makes it suitable for use with psychiatric inpatients. © 2012 Wiley Periodicals, Inc.